Isolation of Some Bioactive Compounds in the Methanol Extract of Ficus exasperata Leaves and the Effect of the Extract on Inflammatory Markers in 1,2 Dimethylhydrazine Induced Colorectal Cancer in Rats. - Okolie, Ngozi Paulinus; Olude, Olayemi Mujidat (Journal of Medical Science, 2025)
Background. Colorectal cancer remains the third dominant cancer and is one of the leading cancer-related deaths in the world. The current investigation explores the chemoprotective roles of Ficus exasperata against inflammation and oxidative stress in 1,2-dimethylhydrazine (DMH)-induced colorectal cancer in rats. Some bioactive compounds were also isolated.Material and methods. Forty-eight Wistar rats were grouped in 8 cages; group 1; control, group 2 was treated with 500mg/kg body weight of extract, group 3 received DMH twice a week, group 4 was treated with both the extract (500mg/kg b.w) and DMH, group 5 was treated with the extract (750mg/kg b.w) and DMH, group 6 was pretreated with the extract before DMH administration, group 7 was given DMH before the commencement of extract and group 8 was given the carcinogen and treated with 12.5mg/kg b.w of 5-fluorouracil simultaneously. Using high-performance liquid chromatography some bioactive compounds were isolated from the leaves extract of Ficus exasperata.Results and conclusions. The bioactive compounds present in high quantity include; alpha-caryophyllene, isoquinoline, quercetin, kaempferol and rutin. After the 12th week, the animals were sacrificed. Total protein, catalase, superoxide dismutase and glutathione peroxidase activities were statistically significantly lower in group 3 (p < 0.05) compared with other groups. Gene expression of the Interleukins and cyclooxygenase 2 were statistically reduced and significant in all the groups except group 3. The extract suppressed the inflammatory cascade and also boosted antioxidant activities. This might be a result of some anticancer compounds that were discovered during the isolation of the compounds present in the plant.